A Novel D-Galacturonate Fermentation Pathway in Lactobacillus suebicus Links Initial Reactions of the Galacturonate-Isomerase Route With the Phosphoketolase Pathway - Valk, Laura C.; Luttik, Marijke A. H.; de Ram, C.; Pabst, Martin; van den Broek, Marcel; van Loosdrecht, Mark C. M.; Pronk, Jack T. (Frontiers in Microbiology, 2020)
D-galacturonate, a key constituent of pectin, is a ubiquitous monomer in plant biomass. Anaerobic, fermentative conversion of D-galacturonate is therefore relevant in natural environments as well as in microbial processes for microbial conversion of pectin-containing agricultural residues. In currently known microorganisms that anaerobically ferment D-galacturonate, its catabolism occurs via the galacturonate-isomerase pathway. Redox-cofactor balancing in this pathway strongly constrains the possible range of products generated from anaerobic D-galacturonate fermentation, resulting in acetate as the predominant organic fermentation product. To explore metabolic diversity of microbial D-galacturonate fermentation, anaerobic enrichment cultures were performed at pH 4. Anaerobic batch and chemostat cultures of a dominant Lactobacillus suebicus strain isolated from these enrichment cultures produced near-equimolar amounts of lactate and acetate from D-galacturonate. A combination of whole-genome sequence analysis, quantitative proteomics, enzyme activity assays in cell extracts and in vitro product identification demonstrated that D-galacturonate metabolism in L. suebicus occurs via a novel pathway. In this pathway, mannonate generated by the initial reactions of the canonical isomerase pathway is converted to 6-phosphogluconate by two novel biochemical reactions, catalysed by a mannonate kinase and a 6-phosphomannonate 2-epimerase. Further catabolism of 6-phosphogluconate then proceeds via known reactions of the phosphoketolase pathway. In contrast to the classical isomerase pathway for D-galacturonate catabolism, the novel pathway enables redox-cofactor-neutral conversion of D-galacturonate to ribulose-5-phosphate. While further research is required to identify the structural genes encoding the key enzymes for the novel pathway, its redox-cofactor coupling is highly interesting for metabolic engineering of microbial cell factories for conversion of pectin-containing feedstocks into added-value fermentation products such as ethanol or lactate. This study illustrates the potential of microbial enrichment cultivation to identify novel pathways for the conversion of environmentally and industrially relevant compounds.